Pelvic Exenteration: Experience from a Rural Cancer Center in Developing World. (8th February 2015) - Dessai, Sampada B.; Balasubramanian, Satheesan; Patil, Vijay M.; Chakraborty, Santam; Bhattacharjee, Atanu; Vikram, Syam
Abstract : Background . Pelvic exenteration (PE) is a morbid procedure. Ours is a rural based cancer center limited trained surgical oncology staff. Hence, this audit was planned to evaluate morbidity and outcomes of all patients undergoing PE at our center. Methods . This is a IRB approved retrospective audit of all patients who underwent PE at our center from January 2010 to August 2013. The toxicity grades were retrospectively assigned according to the CTCAE version 4.02 criteria. Chi-square test was done to identify factors affecting grades 3–5 morbidity. Kaplan Meier survival analysis has been used for estimation of median PFS and OS. Results . 34 patients were identified, with the median age of 52 years (28–73 years). Total, anterior, posterior, and modified posterior exenterations were performed in 4 (11.8%), 5 (14.7%), 14 (41.2%), and 11 (32.4%) patients, respectively. The median time for surgery was 5.5 hours (3–8 hours). The median blood loss was 500 mL (200–4000 mL). CTCAE version 4.02 grades 3-4 toxicity was seen in nine patients (25.7%). The median estimated progression free survival was 31.76 months (25.13–38.40 months). The 2-year overall survival was 97.14%. Conclusion . PE related grades 3–5 morbidity of 25.7% and mortality of 2.9% at our resource limited center are encouraging.